Swirling around filaments: are large-scale structure vortices spinning up dark haloes?. Issue 3 (28th November 2014) - Laigle, C.; Pichon, C.; Codis, S.; Dubois, Y.; Le Borgne, D.; Pogosyan, D.; Devriendt, J.; Peirani, S.; Prunet, S.; Rouberol, S.; Slyz, A.; Sousbie, T.
Abstract: The kinematic analysis of dark matter and hydrodynamical simulations suggests that the vorticity in large-scale structure is mostly confined to, and predominantly aligned with, their filaments, with an excess of probability of 20 per cent to have the angle between vorticity and filaments direction lower than 60° relative to random orientations. The cross-sections of these filaments are typically partitioned into four quadrants with opposite vorticity sign, arising from multiple flows, originating from neighbouring walls. The spins of haloes embedded within these filaments are consistently aligned with this vorticity for any halo mass, with a stronger alignment for the most massive structures up to an excess of probability of 165 per cent. The global geometry of the flow within the cosmic web is therefore qualitatively consistent with a spin acquisition for smaller haloes induced by this large-scale coherence, as argued in Codis et al. In effect, secondary anisotropic infall (originating from the vortex-rich filament within which these lower-mass haloes form) dominates the angular momentum budget of these haloes. The transition mass from alignment to orthogonality is related to the size of a given multi-flow region with a given polarity. This transition may be reconciled with the standard tidal torque theory if the latter is augmented so as to account for the larger scale anisotropic environment of walls and filaments.